Analisis Tingkat Aksesibilitas Pangan Rumah Tangga Petani di Desa Saritani Kecamatan Wonosari Kabupaten Boalemo - Mahmud, Nofita Hasan; Bakari, Yuliana; Hippy, Mohammad Zubair (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This research aims to examine the accessibility of food for farmer households based on physical access, economic access, and social access, and to analyze its influence on food security in Saritani Village, Wonosari District, Boalemo Regency. Data were collected through surveys, interviews, and questionnaires, using primary and secondary data. The purposive sampling method was applied by selecting 38 farmer households (10-20% of the population). Data analysis used descriptive methods and multiple linear regression, with food security as the dependent variable and physical, economic, and social access as independent variables. The results of the descriptive analysis showed that food accessibility, seen from physical, economic, and social aspects, was in fairly good condition. The regression results showed that physical access had a positive and significant effect on food security (regression coefficient = 0.742, significance = 0.004). Economic and social access had a positive but not significant effect (coefficient = 0.145 and 0.585, significance = 0.589 and 0.27). The R-squared value of 0.284 indicates that 28.4% of food security is influenced by these variables, while the rest is influenced by other factors not included in this study.